Impaired ubiquitin–proteasome system activity in the synapses of Huntington's disease mice - Wang, Jianjun (The Rockefeller University Press, 2008)
Huntington's disease (HD) is caused by the expansion of a polyglutamine tract in the N-terminal region of huntingtin (htt) and is characterized by selective neurodegeneration. In addition to forming nuclear aggregates, mutant htt accumulates in neuronal processes as well as synapses and affects synaptic function. However, the mechanism for the synaptic toxicity of mutant htt remains to be investigated. We targeted fluorescent reporters for the ubiquitin–proteasome system (UPS) to presynaptic or postsynaptic terminals of neurons. Using these reporters and biochemical assays of isolated synaptosomes, we found that mutant htt decreases synaptic UPS activity in cultured neurons and in HD mouse brains that express N-terminal or full-length mutant htt. Given that the UPS is a key regulator of synaptic plasticity and function, our findings offer insight into the selective neuronal dysfunction seen in HD and also establish a method to measure synaptic UPS activity in other neurological disease models.